2015
DOI: 10.1590/s1516-89132015060439
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Plasticity and Gas Exchange of Ligustrum lucidumW.T. Aiton in Distinct Light Conditions

Abstract: The objective of this study was to understand the different morpho-physiological strategies of Ligustrum lucidum, an invasive species occurring in Brazilian forest fragments under heterogeneous light conditions. Ten individuals of L. lucidum were selected and evaluated for morphological of the leaves and physiological traits. For morphological parameters were evaluated: length, width, area, angle, petiole length, dried mass, total thickness, palisade parenchyma and spongy parenchyma thickness, abaxial and adax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 54 publications
4
4
0
3
Order By: Relevance
“…All morphological traits except SLA were higher at the forest edge than in the forest understory. At higher light environments, SLA tended to decrease (Li et al 2014, Larcher et al 2015, as observed in the present study. LMA increases with decreasing forest cover, likely due to the increased light availability and water stress (Neyret et al 2016).…”
Section: Variations Of Leaf Traits Under Different Canopy Coversupporting
confidence: 84%
“…All morphological traits except SLA were higher at the forest edge than in the forest understory. At higher light environments, SLA tended to decrease (Li et al 2014, Larcher et al 2015, as observed in the present study. LMA increases with decreasing forest cover, likely due to the increased light availability and water stress (Neyret et al 2016).…”
Section: Variations Of Leaf Traits Under Different Canopy Coversupporting
confidence: 84%
“…Considering light as one of the most limiting factors for photosynthesis (Chazdon & Fetcher, 1984), seedlings submitted to full sunlight showed greater photosynthesis (Table 1). Larcher et al (2015), obtained similar results in Ligustrum lucidum, where it demonstrated lower values of photosynthesis in the shade.…”
Section: Resultssupporting
confidence: 58%
“…The different luminous environments influenced the physiological and anatomical parameters. Several authors have observed the effect of luminosity on these parameters in tree species (Larcher et al, 2015;Felsemburgh et al, 2016;Dardengo et al, 2017), and Guazuma ulmifolia is considered a pioneer species tolerant to greater light (Lorenzi, 1992). We observed that G. ulmifolia showed characteristics such as increased photosynthetic rate, stomatal conductance and anatomical features such as thickness of parenchyma tissues, which refer to pioneer species tolerant to high light (Aragão et al, 2014;Dardengo et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…O incremento da espessura do mesofilo através do investimento em parênquima lacunoso tem sido discutido como uma estratégia de otimizar processos fotossintéticos, visto que o espaço intercelular ocorrente no parênquima lacunoso favorece o transporte de gases no mesofilo (Tian et al 2016) e complementa a eficiência de absorção luminosa. A combinação de parênquimas paliçádico e lacunoso espessos, observada nas populações de S. campestris, aumenta a assimilação e, por consequente, o crescimento das plantas (Larcher et al 2015). Em adição, a maior produção de tecido fotossintético em indivíduos da restinga herbácea, se comparados às demais formações de restinga, pode ser resultante da melhor absorção de K, Mg e P, proporcionado pelo maior teor de Ca neste local, efeito denominado como "efeito Viets" (Viets 1944).…”
Section: Discussionunclassified